Um mar de histórias: memória, identidade e territorialidade no Poço da Draga - Gomes, Marília Passos Apoliano (2019)
This research seeks to understand the relationships between memory, identity and territoriality, based on the case study of Poço da Draga, in Fortaleza, Ceará, Brazil. This is an area in which there are several community events in which a large part of the residents argue that the locality is a hundred years old, bearing a strong memory about itself and about the city of Fortaleza, and as such should be respected and preserved. In the thesis, these events are analyzed in detail, in order to understand their relevance to the construction of memory and community identity, as well as to study the relationship established in that area between territoriality, identity and memory. The centrality of the sea is another significant factor in the area studied, which is why it is said that there exists a "sea of memories" in the light of Hannah Arendt. It is a qualitative research, whose methodological procedures focused on participant observation, semi-structured interviews, field diary analysis and literature review. Fieldwork was developed in concentrated periods of a few months between 2014 and 2018, with a higher incidence between 2015 and 2017, totaling between nine and ten months of systematic observation. The comings and goings to the field made possible the permanence in the long term, which proved to be satisfactory. The theoretical framework was woven around Ecléa Bosi, Frederick Bartlett, Hermann Ebbinghaus, Jacques Le Goff, Jöel Candau, Linda Gondim, Manuela Carneiro da Cunha, Marc Bloch, Marcelo Lopes de Souza, Marcos Alvito, Maurice Halbwachs, Michael Pollak, Michel de Certeau, Milton Santos, Paul Connerton, Paul Ricoeur, Pierre Bourdieu, Pierre Nora, Roberto Cardoso de Oliveira, Rogério Haesbaert and Stuart Hall. As a result, I understood that the existence of anniversaries of the locality, the wheel of the Guardians of memory and the guided tours is essential for the processes of memory and identity construction in the area. They are singular events that are promoted by the residents, endowed with much ritualistic, and quite significant about the locality. They are events of memorial registration, it being impossible to speak of separate memory of identity. In addition, all community acts also have registration in the territory, since they always develop in one of the microterritories, as will be discussed.